2022
DOI: 10.1371/journal.pone.0257963
|View full text |Cite
|
Sign up to set email alerts
|

Dry heat sterilization as a method to recycle N95 respirator masks: The importance of fit

Abstract: In times of crisis, including the current COVID-19 pandemic, the supply chain of filtering facepiece respirators, such as N95 respirators, are disrupted. To combat shortages of N95 respirators, many institutions were forced to decontaminate and reuse respirators. While several reports have evaluated the impact on filtration as a measurement of preservation of respirator function after decontamination, the equally important fact of maintaining proper fit to the users’ face has been understudied. In the current … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
1
4
0
3
Order By: Relevance
“… 19 Although the availability of N95s has increased significantly over the course of the pandemic, prices have also increased and uncertainty remains in how the COVID-19 pandemic will continue to evolve. Nevertheless, studies have increasingly suggested that N95s can be decontaminated and reused 20 , 21 ; taken together with our findings implies that healthcare systems could prioritize reuse, particularly for OR procedures.…”
Section: Discussionsupporting
confidence: 60%
“… 19 Although the availability of N95s has increased significantly over the course of the pandemic, prices have also increased and uncertainty remains in how the COVID-19 pandemic will continue to evolve. Nevertheless, studies have increasingly suggested that N95s can be decontaminated and reused 20 , 21 ; taken together with our findings implies that healthcare systems could prioritize reuse, particularly for OR procedures.…”
Section: Discussionsupporting
confidence: 60%
“…Embora a autoclavagem (ou seja, vapor a ~121°C e > 15 PSI) seja um método comprovado de esterilização da maioria dos patógenos, não é viável para descontaminação de respiradores N95 usados porque o calor úmido pode degradar a eficiência do filtro. No meio da cultura, SARS-CoV-2 foi relatado como inativado pelo tratamento de calor seco em apenas 5 minutos a 70°C e a exposição do SARS-Cov-2 em superfícies para o calor seco a > 70°C por >30 minutos é suficiente para alcançar uma redução de ≥ 3 log de títulos virais, atendendo às recomendações da Food and Drug Administration, ou Administração de Alimentos e Medicamentos (FDA) para FFR (Yuen et al, 2022).…”
Section: Resultsunclassified
“…Os respiradores autoclavados falharam no teste de ajuste do respirador e sugeriram que a mudança na eficiência da filtragem é de até 7,73%. No entanto, a análise do material respirador não corrobora mudanças significativas no material de filtragem que poderiam levar a essas reduções na eficiência da filtragem (Yuen et al, 2022).…”
Section: Resultsunclassified
“…Previous research proposed a recycling technique for mask waste using ultraviolet radiation disinfectant and autoclaving [37,38]. This contradicts [39,40], which finds that disposable medical masks are difficult to recycle because they can potentially contain viruses and bacteria.…”
Section: Introductionmentioning
confidence: 99%